2018
DOI: 10.1111/lcrp.12141
|View full text |Cite
|
Sign up to set email alerts
|

Death penalty decision‐making: Fundamentalist beliefs and the evaluation of aggravating and mitigating circumstances

Abstract: Purpose Jurors’ religious characteristics are related to death penalty attitudes and verdicts. Jurors’ religious characteristics might also relate to endorsements of aggravating circumstances (aggravators) and mitigating circumstances (mitigators)—factors that make a defendant more or less deserving of the death penalty, respectively. The purpose of this research was to assess the extent to which religious fundamentalism was related to endorsement and weighing of aggravators and mitigators and subsequent death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…As for observer characteristics, our hypothesis was only partially supported: The only variable that contributed to the prediction of CC support was observer religiosity. As previous studies suggested (e.g., Miller, 2016, 2017;Yelderman et al, 2019), our finding indicates that secular respondents were less punitive and chose CC as appropriate punishment more frequently than religious respondents. The contribution of religiosity is even more distinctive in light of the non-significant association between CC support and observer gender, age, education, ethnicity, economic status, and political affiliation.…”
Section: Individual Factorssupporting
confidence: 82%
“…As for observer characteristics, our hypothesis was only partially supported: The only variable that contributed to the prediction of CC support was observer religiosity. As previous studies suggested (e.g., Miller, 2016, 2017;Yelderman et al, 2019), our finding indicates that secular respondents were less punitive and chose CC as appropriate punishment more frequently than religious respondents. The contribution of religiosity is even more distinctive in light of the non-significant association between CC support and observer gender, age, education, ethnicity, economic status, and political affiliation.…”
Section: Individual Factorssupporting
confidence: 82%
“…Although fundamentalists appear resistant to evidence that would deem murder less worthy of the death penalty, they seem to evaluate aggravating circumstances similarly to non-fundamentalists. Th is is also consistent with the threshold approach to understanding the relationship between fundamentalism and death sentencing" (Yelderman, West, Miller, 2019).…”
Section: Absence or Presence Of Correlation Between Fundamentalism Ansupporting
confidence: 76%
“…Religion is another central factor associated with attitudes toward offenders (Bohm, 1987; Falco & Turner, 2014). Citizens who rate themselves as more religious tend to attribute less responsibility to husbands who beat their wives (e.g., Haj-Yahia & Zaatut, 2018), are more supportive of the juvenile death penalty (Skovron, Scott, & Cullen, 1989), and are generally more punitive (Yelderman & Miller, 2017; Yelderman, West, & Miller, 2018). The few studies that examined religion mostly focused on Christian religious affiliation (Rade, Holland, Gregory, & Desmarais, 2017; Wozniak & Lewis, 2010) and present mixed results.…”
Section: Observer Ethnicity and Religionmentioning
confidence: 99%